Supersuming Subsumption: Theory and Politics - Briziarelli, Marco (Historical Materialism Book Series, 2024)
The main purpose of Supersuming Subsumption is to extrapolate from the Marxian understanding of subsumption - and the author's own socially historically situated reading of it - a dynamic and holistic theory of capitalist social power relations.